Condição da colônia e alterações bionômicas em Geotrigona inusitata (Apidae, Meliponinae) - Lacerda, Lenira de Melo; Zucchi, Ronaldo; Zucoloto, Fernando Sérgio (Acta Biológica Paranaense, 1991)
Condição da colônia e alterações bionômicas em Geotrigona inusitata (Apidae, Meliponinae)